Epidemiological Pattern and Clinical Outcomes of Measles among Children Managed at Modibbo Adama University Teaching Hospital, Yola, North-East Nigeria: A Retrospective Study - Hayatu Ahmad (FUDMA Journal of Sciences, 2026)
Measles is a vaccine-preventable disease that continues to cause substantial childhood morbidity and mortality in Nigeria, particularly in the north, where vaccination coverage remains suboptimal, population displacement is widespread, and access to healthcare is limited. Objectives: This study aimed to describe the epidemiological pattern, vaccination status, clinical complications, and outcomes of measles among children managed at Modibbo Adama University Teaching Hospital (MAUTHY), Yola, Adamawa State, North-East Nigeria. Methods: A retrospective cross-sectional study was conducted among 22 children aged 1 month to 17 years admitted with clinical measles between January and December 2025. Data were extracted from medical records using a structured form and analysed with IBM SPSS Statistics version 21; Fisher’s exact test was used for categorical associations (p < 0.05). Results and Discussion: Children under five years accounted for 86.4% of admissions; children aged 1–4 years formed the largest age group (54.5%). Sex distribution was equal. Most children (81.8%) were unvaccinated or incompletely vaccinated. A marked seasonal peak occurred in March–April, accounting for 68.2% of cases and all deaths. Bronchopneumonia (90.9%), severe acute malnutrition (81.8%), and diarrhoea (68.1%) were the commonest complications. Six children died, yielding a case fatality rate of 27.3%; four deaths occurred within 24 hours of admission. No statistically significant association was detected between age group and outcome (p = 1.000). Conclusion: Measles imposes a severe, preventable burden on children in Adamawa State. Strengthening routine immunization, nutritional support, and early care-seeking behaviour are essential priorities.